(untitled) (Journal Of Educational and Psychological Researches, 2022)
This research discusses the developmental role of the social worker in providing care for children at risk. The research is desicriptive in nature include both the theoretical and field aspects. The theoretical aspect focuses on the characteristics and requirements of these children and what forms and implications are exposed to them by society, what is the developmental role of the social worker in the rehabilitation of this group. As for the field aspect, the study sample took a (40) social workers who working in Aiwa institutions inside Baghdad. A questionnaire of (14) questions was used as tool to collect the needed data.